Framing COVID-19 and the movement control order: between social responsibility and editorial ideology - Mohamed, Shafizan; Idid, Syed Arabi (Secholian Publication, 2022)
Pandemics pose significant global risks. If the aftermath of a large-scale health crisis is not carefully contained, it can be catastrophic. In times like this, the media plays an important role in educating the public and upholding social order by covering news that is both insightful and positive. This study examines media coverage of the COVID-19 health crisis in Malaysia during the country's Minimal Control Order (MCO) period using a framing theory perspective. According to the results of a content analysis of The Star Online (N=870) and Malaysiakini Bahasa (N=870), issues concerning the technical implementation of the Movemenet Control Order (MCO) and the economy dominated the news. Despite the parallels in the topics covered, the study also discovered that when it came to framing the news, The Star was more optimistic about how the crisis is progressing than Malaysiakini, suggesting that even during a pandemic, local newspapers couldn't wander too far from their political and ideological positions.